Identification of cytoplasm types in accessions of the family Brassicaceae (Brassicaceae Burnett) with DNA markers - E. A. Domblides; A. S. Domblides; T. V. Zayachkovskaya; L. L. Bondareva (Вавиловский журнал генетики и селекции)
Identification of cytoplasm types with the use of molecular markers enables to simplify the parent line pair selection for hybrid development based on CMS. Forty accessions of the family Brassicaceae (Brassicaceae Burnett) were analyzed with 22 pairs of PCR primers taken from previous research. Seven types of cytoplasm (Ogura, Ogu-NWSUAF, nap, pol, cam, rad, ole) were observed among breeding accessions using standard and multiplex PCR technique. The sequence of PCR products that differentiated different types of sterile cytoplasm confirmed the presence of three genes, orf138, orf222, and orf224, in mitochondrial DNA associated with exhibition of CMS. The accession of Nappa cabbage (Brassica rapa Pekinensis Group) had two genes, orf138 and orf222, which corresponded to cytoplasm Ogu-NWSUAF. All accessions carrying Ogura cytoplasm had the 417 bp fragment, which was 100 % identical to the mitochondrial orf138 gene sequence corres- ponding to Type А (formerly nine sequence Types, from A to I, had been identified). An exception was the accession of white head cabbage Tekila F1 with a new allelic variant of orf138 gene, which combined the 39-bp deletion typical of the Type F orf138 sequence and two nonsynonymous substitutions, A→T and G→A, at positions 95 and 99, respectively.